AWAKENING CHARACTERISTICS AND RECOVERY OF COGNITIVE FUNCTION IN PATIENTS UNDERGOING SHORT SURGICAL PROCEDURES: COMPARISON BETWEEN DESFLURANE AND PROPOFOL - BASHA, FERNAZ; S, PARTHASARATHY; CHARLES S, ANTONY JOHN; M, RAVISHANKAR; KUMAR VR, HEMANTH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Early awakening and recovery of the cognitive function improves post-operative outcome and early discharge of the patients. Desflurane and Propofol offer rapid emergence from anesthesia. We compared the awakening and recovery of cognitive function between these two agents. Methods: A total of 50 patients aged 30–60 years belonging to ASA 1 and 2 were studied. In both the groups baseline, Mini Mental State Examination (MMSE) score was recorded and were induced with Target controlled infusion (TCI) of Propofol to achieve plasma site concentration (Cp) of 6 mcg/ml. Group P continued with TCI Propofol Cp 3 mcg ml-1 and in group D, TCI was stopped and started Desflurane 6% end tidal concentration followed by Desflurane 3%. Hemodynamic variables were noted and after stopping the agent, time to eye open, squeeze hands, removal of laryngeal mask airway, state name, and modified Aldrete score were noted. MMSE score was recorded 1, 6, and 24 h postoperatively. Results: Awakening time was significantly shorter in duration in Desflurane group compared to Propofol. The mean time to eye open in the Propofol group was 10.41±2:31 min and Desflurane group was 06.21±01.42 min (***p=0.000). There was an increase in the mean MMSE score postoperatively at 6 h and 24 h interval when compared to the baseline within the groups. However, there was no difference in recovery of cognitive function between the two groups. Conclusion: The use of inhalational agent Desflurane provided shorter awakening time than intravenous Propofol in short surgical procedures but the recovery of cognitive function was comparable. There were no significant side effects.